Hubungan antara Perasaan Bersalah dan Keberhasilan Pengobatan Lupus - Romaito Nasution; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Milna Sari (An-Najat, 2024)
This study analyzes the relationship between guilt and treatment outcomes in lupus patients through a meta-analysis of 15 studies (N = 2,876). The results indicate a significant negative correlation (r = -0.32, 95% CI [-0.39, -0.25], p < 0.001) between levels of guilt and lupus treatment success. Moderator analysis revealed a stronger relationship in younger patients (β = 0.015, SE = 0.006, p = 0.013) and those with a shorter disease duration (β = -0.021, SE = 0.009, p = 0.019). The strongest correlation was found in the disease activity dimension (r = -0.38, 95% CI [-0.46, -0.29]) compared to quality of life (r = -0.30, 95% CI [-0.38, -0.21]) or medication adherence (r = -0.25, 95% CI [-0.34, -0.15]). Furthermore, mediation analysis revealed that coping strategies mediated 34% of the effect of guilt on treatment outcomes. Longitudinal findings confirmed that a decrease in guilt is associated with improved treatment outcomes (r = -0.29, 95% CI [-0.41, -0.16], p < 0.001). These findings extend Witvliet et al. (2001) regarding the impact of guilt on health and support Engel's biopsychosocial model (1977) in the context of lupus. Unlike Navarrete-Navarrete et al. (2010), which focused on a single case, this research provides large-scale quantitative evidence. Finally, the primary novelty of this study lies in identifying the non-linear relationship between guilt levels and treatment outcomes, as well as the moderating role in psychological interventions (Q = 4.12, df = 1, p = 0.042). Thus, the findings underscore the importance of integrating guilt assessment and management in lupus care, supporting a holistic approach that combines psychological interventions with medical treatment.